2015
DOI: 10.1007/s40273-015-0316-5
|View full text |Cite
|
Sign up to set email alerts
|

Economic and Quality-of-Life Implications of Non-Alcoholic Fatty Liver Disease

Abstract: Non-alcoholic fatty liver disease (NAFLD) is a very common chronic liver disease worldwide, is on the rise following the trend of increasing prevalence of obesity, is the second most common indication for liver transplantation, and is an important cause for hepatocellular carcinoma. Despite the increasing recognition of NAFLD as an important chronic liver disease, little has been published on the economic and health-related quality of life (HR-QOL) impact of NAFLD. We reviewed the current literature related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 44 publications
0
70
0
1
Order By: Relevance
“…Within the twelve studies that have mentioned the included obesity-related diseases, one study, by Su et al [31], included obesity-related liver diseases, such as non-alcoholic fatty liver disease (NAFLD), liver fibrosis and cirrhosis of the liver, which are also associated with obesity [75,76]. For example, NAFLD, a very common chronic liver disease worldwide, is on the rise following the trend of increasing prevalence of obesity, and is the second most common indication for liver transplantation, and an important cause of hepatocellular carcinoma [77]. Also, hepatic steatosis is known to be an associated comorbidity of obesity [78].…”
Section: Discussionmentioning
confidence: 99%
“…Within the twelve studies that have mentioned the included obesity-related diseases, one study, by Su et al [31], included obesity-related liver diseases, such as non-alcoholic fatty liver disease (NAFLD), liver fibrosis and cirrhosis of the liver, which are also associated with obesity [75,76]. For example, NAFLD, a very common chronic liver disease worldwide, is on the rise following the trend of increasing prevalence of obesity, and is the second most common indication for liver transplantation, and an important cause of hepatocellular carcinoma [77]. Also, hepatic steatosis is known to be an associated comorbidity of obesity [78].…”
Section: Discussionmentioning
confidence: 99%
“…97100 Adults with NAFLD had had worse physical and mental health scores compared to the U.S. population with and without chronic illness. 99 Moreover, among adults with NAFLD, those with NASH reported lower physical health, but not mental health, compared to subjects with fatty liver disease without NASH.…”
Section: Associated Co-morbidities Of Nafldmentioning
confidence: 99%
“…Modeling can be used as a tool to take into account existing epidemiology parameters to forecast disease burden. Several recent analyses assessed the disease and economic burden associated with NASH [10][11][12]. Prior studies were based on existing data reported in the literature, but such studies are confounded by varying case definitions, diagnostic techniques, and staging used for NAFLD / NASH; as well as relatively small and varying sample populations.…”
Section: Introductionmentioning
confidence: 99%